2013
DOI: 10.1590/s0004-28032013000100008
|View full text |Cite
|
Sign up to set email alerts
|

Hfe Mutations and Iron Overload in Patients With Alcoholic Liver Disease

Abstract: -Context -Alcoholic liver disease (ALD) is generally associated with iron overload, which may contribute to its pathogenesis, through increased oxidative stress and cellular damage. There are conflicting reports in literature about hemochromatosis (HFE) gene mutations and the severity of liver disease in alcoholic patients. Objectives -To compare the prevalence of mutations in the hemochromatosis (HFE) gene between patients with ALD and healthy controls; to assess the relation of HFE mutations with liver iron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 33 publications
(30 reference statements)
0
17
0
Order By: Relevance
“…A HFE mutation has been detected more frequently in patients with ALD and hepatic iron accumulation than in patients with ALD and no hepatic iron accumulation (odds ratio, 17.23; 95% CI: 2.09‐142.34; P = 0.008), but the HFE mutation has not been associated with increased hepatic fibrosis, disease severity, or inflammatory activity . Other studies have demonstrated that the occurrence of a single HFE mutation in ALD has not increased the hepatic iron content, frequency of fibrosis, or predisposition for severe ALD .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…A HFE mutation has been detected more frequently in patients with ALD and hepatic iron accumulation than in patients with ALD and no hepatic iron accumulation (odds ratio, 17.23; 95% CI: 2.09‐142.34; P = 0.008), but the HFE mutation has not been associated with increased hepatic fibrosis, disease severity, or inflammatory activity . Other studies have demonstrated that the occurrence of a single HFE mutation in ALD has not increased the hepatic iron content, frequency of fibrosis, or predisposition for severe ALD .…”
Section: Resultsmentioning
confidence: 98%
“…Serum ferritin levels and transferrin saturations are increased in 63% and 29% of patients with alcoholic liver disease (ALD), and the results are significantly higher than in healthy individuals ( P < 0.05) (Table ) . Stainable hepatic iron in parenchymal and reticuloendothelial cells has been demonstrated in 52% of patients with ALD, and severe (grade 3‐4) iron deposition has been present in 22% of liver explants .…”
Section: Resultsmentioning
confidence: 99%
“…The H63D variant, which we found most frequently associated with pulmonary fibrosis in the current study patients, is associated with disease with very low penetrance, even when homozygous, when compared with the C282Y allele, which is the more commonly causative allele of the autosomal recessive type 1 hereditary haemochromatosis. However, both the C282Y and the H63D variants are associated with increased susceptibility to liver cirrhosis in alcohol liver disease and viral hepatitis [20,21]. Is the carriage of HFE gene variants a cause of dysregulated cellular iron levels in IPF?…”
Section: Discussionmentioning
confidence: 99%
“…C282Y and H63D are common allelic variants of HFE, with allele frequencies of 3.8±0.7% and 13.6±1.3%, respectively, in Europe, and lower frequencies for C282Y in southern Europe and Italy [19]. Importantly, they have been reported, albeit not univocally, to confer greater susceptibility to liver iron overload and cirrhosis upon heterozygous carriers exposed to chronic inflammation, such as in viral hepatitis or alcohol-related liver disease [20,21]. With this as a background, and with the knowledge that a number of exposures have been implicated as possible risk factors for IPF [22,23], we hypothesised a role as susceptibility factors to HFE allelic variants, due to their potential for dysregulated iron accumulation and exaggerated generation of oxygen radicals.…”
Section: Introductionmentioning
confidence: 99%
“…The hepatic iron loading observed is generally modest, with infrequent cases of severe iron loading (193,194). The iron accumulation in ALD appears to be independent of HFE and other genetic mutations (195).…”
Section: Iron Overload In Aldmentioning
confidence: 90%